Manajemen Laba dan Tindakan Mitigasi Pada Perbankan Syariah - Nuryani Ambri; Annisa Awaliah; Arif Wansa; Muhammad Fahrul Dzulfikar; Mey Tekla Kelyombar (PT Maju Malaqbi Makkarana, 2023)
Earnings management is a strategy carried out by organizations with the intention that profits in each period are always large. This is the case for financial institutions based on Islamic principles and Islamic business which, depending on their underlying motivation, use the concept of profit as the difference between income and expenses. To demonstrate the success of Islamic banks in carrying out their business operations, this study finds and examines the existence of earnings management in the financial statements of Islamic banks. Utilizing subjective expressive strategies by collecting documentary information, this study will reveal the current reality of the tasks of Islamic banks and benefit executives by supervisors. This study provides an explanation of this contradiction and a response to the issue of earnings management in Islamic banking. This study uses written studies to examine the details of the problem. Data reduction techniques such as summarizing, choosing the most important things, focusing on the most important things, and then drawing conclusions are used in the analytical method which is a descriptive qualitative method. The discussion revealed that earnings management is a common practice in Islamic banking. Using qualified and reputable auditors to review a bank's financial statements and fully implementing corporate governance are two ways Islamic banking can reduce risk. Agency theory, signal theory, and the concept of earnings management as a whole are some of the ideas that guide managers' actions in earnings management. Risk is something that is dubious in the absence of data and investigation. The term